THE EFFECT OF PERSON-ORGANIZATION FIT ON JOB SATISFACTION: THE ROLE OF WORKPLACE HAPPINESS - Aslıhan Yıldız; Hasan Hüseyin Uzunbacak (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In the study, it was aimed to examine the mediating role of workplace happiness in the effect of person-organization fit on job satisfaction. In this context, a literature review on the concepts of happiness, workplace happiness, person-organization fit and job satisfaction was added to the research. The sample of the research consists of 468 white collar employees from 18 enterprises operating in the textile industry in Denizli Organized Industrial Zone. The data procured by using simple sampling method were obtained by making questionnaire to the employees. The survey consists of 20 items about person-organization fit (four items), job satisfaction (five items), workplace happiness (five items), and determining the demographic characteristics of the respondents (6 items). SPSS 22 and AMOS 21 softwares were used in the data analysis of the research. Structural Equation Model was use. It was found out that employees with high person-organization fit experienced higher levels of happiness at work and job satisfaction. In addition, happiness at work had a mediating role between the person-organization fit and job satisfaction.